A Participação da sociedade na relação processual: uma análise sobre o amicus curiae e suas repercussões em casos trabalhistas - CAVALCANTE JÚNIOR, José Leite (2022)
The presente work aims to analyze the participation of people, agencies and entities as intervening in legal proceedings, as a way to better provide elements for the formation of the judge’s conviction and, with that, the judge to make better technical decisions. To this end,the amicus curiae institute, its legal nature, its application in today’s Brazilian procedural system and its acceptance before the Federal Supreme Court will be analyzed. In addition, it will be observed how this institute can collaborate for access to justice, for the principles of adversarial and broad defense, for procedural cooperation and, finally, for the democratization and better functioning of the Brazilian Judiciary. Finally, it will be seen how the “friend of the court” has been accepted in labor claims that are being processed before the higher courts, especially ADI 6363, which, when judged in April 2020, contributed a lot to the discussion about labor relations in a pandemic contexto hitherto incipiente. In this sense, it will be demonstrated how the amicus collaborated to further enrich the debate on such na importante topic.